BRAND LOVE AS A MEDIATION OF THE INFLUENCE OF NOVELTY AND EXPERIENCE ON REVISIT INTENTION AT THE JOGJA TOURISM CITY - Saktiana, Galuh Mira (International Journal of Application on Economics and Business, 2024)
This study aims to test the effect of novelty and experience on the intention of visiting the Jogja tourism city. The sample was carried out by the nonprobability method, where the population was unknown. The sample size used is as many as 250 respondents with sampling techniques, namely purposive sampling with the criteria that the sample made by respondents is tourists who have visited the city of Jogja before. This study uses a questionnaire that is distributed to do the Google Form The research design used is quantitative descriptive with cross sectional design. The analysis tool used is SEM PLS. Testing the measuring instrument using the validity test, including convergent and discriminant validity, then followed by reliability testing. This research has 7 hypotheses in it and the results of this study are novelty does not affect the revisit intention the Jogja Tourism City, while 6 other hypotheses are accepted.